A study of constant air volume and variable air volume air conditioning system for computer rooms of Block C24 [electronic resource] - 327630 Muhammad Faizal Mahadi; Fakulti Kejuruteraan Mekanikal (Skudai : Universiti Teknologi Malaysia, 2007)
Project Paper (Sarjana Muda Kejuruteraan Mekanikal) - Universiti Teknologi Malaysia, 2007